Relationship between vasomotor symptoms and metabolic syndrome in postmenopausal women - YILDIZHAN, BEGÜM; PEKİN, TANJU (SAGE PUBLICATIONS LTD, 2018)
Objective: This study was performed to compare the vasomotor symptoms and bone mineral density of postmenopausal women with and without metabolic syndrome. Methods: We performed a cross-sectional study of 200 postmenopausal women attending routine health check-ups at Marmara Faculty of Medicine Pendik Training and Research Hospital from June 2015 to December 2015. The vasomotor symptoms scored were hot flashes and night sweats. Metabolic syndrome was defined using the consensus criteria of the International Diabetes Federation and the American Heart Association/National Heart, Lung, and Blood Institute. Results: Women with vasomotor symptoms had no metabolic syndrome and were younger than those without vasomotor symptoms. There was no significant difference in vasomotor symptoms between patients with osteopenia in the femoral neck, total femur, and spine and patients with normal bone mineral density. The vasomotor symptoms were similar between smokers and nonsmokers. Conclusion: The presence of metabolic symptoms is inversely associated with metabolic syndrome in postmenopausal women. Lipid abnormalities and a high body mass index may be important metabolic components associated with these symptoms. No relationship is present between vasomotor symptoms and the bone mineral density of the spine, femoral neck, and total femur.
Keywords: Menopause; vasomotor symptoms; metabolic syndrome; bone mineral density; hot flashes; night sweats; BONE-MINERAL DENSITY; CARDIOVASCULAR-DISEASE; MENOPAUSAL SYMPTOMS; RISK-FACTORS; ASSOCIATION; HEALTH